Problem Based Learning as Part of Student-Centered Learning - Mudrikah, Andriyani (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
In the 21st century, learning is different from the previous century, where in the learning process students not only memorize knowledge but they are required to be active and creative in thinking. The purpose of this study is to describe the concepts of Problem Based Learning and Student-Centered Learning. The result of this study is that Problem Based Learning is part of Student-Centered Learning where the learning process in Problem Based Learning focuses more on students as learning people.